Pengembangan Usaha Mikro Kecil Menengah (UMKM) Tempe di Desa Cimaung - Doni Pernanda; Meddy Robiansya; Difa Wiratama; Imelda Al Fathir (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Efforts to introduce and develop Micro, Small and Medium Enterprises (MSME) have an important role and strategy in national economic development. In addition to playing a role in economic growth, it also plays a role in the absorption of labor on a large scale. Cimaung village has a very wide agricultural land. So that the community can take advantage of the results of their village to raise village MSME. This Community Service Activity (MSME) is carried out with outreach activities and implementation methods such as observation and interviews, lectures and discussions, as well as demonstrations and practices. Based on the phenomenon of existing thinking, efforts are needed to increase public interest in MSME and provide motivation to the community to continue to run a business or take advantage of existing opportunities to open a business. This outreach also explained the importance of marketing on social media and also utilizing technology for business development